A system dynamics model for rice farmers’ livelihood resilience in Indonesia coastal area - Nila Ardhyarini H. Pratiwi; Mahawan Karuniasa; Djoko Santoso Abi Suroso (Trend and Future of Agribusiness, 2025)
Background: Climate change has become a major global challenge, particularly for vulnerable archipelagic and agrarian countries like Indonesia. Many rice fields in coastal areas—including Cirebon District—are highly exposed to extreme climate events such as prolonged droughts. These conditions disrupt rice farmers’ livelihood systems and reduce their income, threatening their overall livelihood resilience. Methods: This study employed a mixed-methods approach by integrating qualitative and quantitative data to develop a system dynamics model. The model explored interactions between livelihood capital assets, self-organization, learning capacity, and climate conditions. Livelihood resilience was assessed through farmers’ income as a key livelihood outcome. Finding: Model outcomes show that rice farmers’ livelihood systems are not resilient to drought impacts, as their income consistently falls below the ideal threshold. Drought events disrupt livelihoods and lead to income losses, and current farmer-led adaptation efforts are insufficient to improve resilience. Without intervention from government or relevant stakeholders, the livelihood system is projected to remain non-resilient in the future. Conclusion: Rice farmers in Cirebon District lack adequate resilience to cope with drought impacts. Strengthening livelihood resilience requires targeted government interventions to improve critical subsystems, including irrigation governance, crop insurance mechanisms, adaptive farming capacity, and access to climate information. Novelty/Originality of this article: This study provides a system-level understanding of rice farmers’ livelihood resilience by integrating system dynamics modeling with mixed-methods data. It offers a holistic analysis of how livelihood assets, learning capacity, self-organization, and climate stressors interact, and identifies leverage points for policy intervention in drought-prone coastal regions.